Composite Structures of d-Wave and s-Wave Superconductors (d-Dot): Analysis Using Two-Component Ginzburg-Landau Equations - Kato, Masaru; Ishida, Takekazu; Koyama, Tomio; Machida, Masahiko (IntechOpen, 2012)
None